Golfer's swing leads to a spontaneous subcapsular liver haematoma. (19th June 2013) - Lumley, S; Slesser, A A P; Saunders, M; Warren, S
Abstract : We report the rare case of a patient presenting with a spontaneous hepatic subcapsular haematoma after playing golf. The patient had no underlying predisposing conditions. A CT scan of the abdomen/pelvis demonstrated a 1 cm deep low-attenuation subcapsular collection around the anterolateral aspect of the liver. The patient was treated conservatively and was discharged from inpatient care after 72 h. This is only the second reported case of a spontaneous subcapsular haematoma.